Soluble and insoluble ternary complexes of serum proteins with polyanions in the presence of Cu2+ in water - (:unkn) unknown (WILEY, 1996)
Complex formation between polyacrylic acid (PAA) and bovine serum albumin (BSA), human serum albumin (HSA), hemoglobin (Hb), globin (Gl), and, respectively, transferrin (Tr), were studied in neutral water. Water-soluble and insoluble complexes are formed upon addition of divalent copper ions to the solution. The contacts between proteins and PAA are achieved via chelate unit formation in which the copper ions are located at the center. The solubility of the polycomplexes depends on the nature of proteins acid correlates with their isoelectric points (pI). In the mixtures of Hb-Cu2+-PAA and Gl-Cu2+-PAA, insoluble complexes are formed at pH = pI starting with very low concentrations of Cu2+ (n(Cu)/n(AA) less than or equal to 0.01) On the other hand, these polycomplexes remain soluble at pH > pi. BSA, HSA, and Tr form soluble ternary polycomplexes at neutral water (pH 7). The formation of the polycomplexes in the mixture BSA-Cu2+-PAA was intensively studied by titration, HPLC, electrophoretic, and spectrophotometric methods. The solubility, composition, and stability of these polycomplexes depend on metal/polymer and protein/polymer ratio. Insoluble polycomplexes are formed when concentration of Cu2+ reaches a critical value (n(Cu)/n(AA) greater than or equal to 0.25). At this concentration of Cu2+, phase separation takes place, starting with very low concentration of protein in the system. Over the critical ratio of the protein/polymer, the mixture again exhibits water-soluble character. The pattern of distribution of Cu2+ between PAA coils and of protein globules between polymer-metal complex particules appeared to follow the self-assembly principle. A hypothetical structural scheme for the formation of soluble and insoluble ternary polycomplexes is proposed. (C) 1996 John Wiley & Sons, Inc.
Keywords: ALBUMIN